2018
DOI: 10.1371/journal.pone.0190446
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of positive selection in African Butana and Kenana dairy zebu cattle

Abstract: Butana and Kenana are two types of zebu cattle found in Sudan. They are unique amongst African indigenous zebu cattle because of their high milk production. Aiming to understand their genome structure, we genotyped 25 individuals from each breed using the Illumina BovineHD Genotyping BeadChip. Genetic structure analysis shows that both breeds have an admixed genome composed of an even proportion of indicine (0.75 ± 0.03 in Butana, 0.76 ± 0.006 in Kenana) and taurine (0.23 ± 0.009 in Butana, 0.24 ± 0.006 in Ken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 73 publications
10
59
0
Order By: Relevance
“…Our findings indicated that pathways associated with production and mechanisms of environmental adaptation, such as immune response, male reproduction, energy production and heat stress, may be under selection in Ugandan goat breeds. This is in agreement with findings in East African Short -horn Zebu cattle Bahbahani et al, 2017;Bahbahani et al, 2018), South African cattle (Makina et al, 2015) and indigenous goats in Morocco and Egypt . Gene ontology analysis shows that multiple pathways are expressed in the Ugandan goat breeds, which may indicate an adaptation to varied environmental conditions.…”
Section: Gene Enrichment Analysissupporting
confidence: 92%
“…Our findings indicated that pathways associated with production and mechanisms of environmental adaptation, such as immune response, male reproduction, energy production and heat stress, may be under selection in Ugandan goat breeds. This is in agreement with findings in East African Short -horn Zebu cattle Bahbahani et al, 2017;Bahbahani et al, 2018), South African cattle (Makina et al, 2015) and indigenous goats in Morocco and Egypt . Gene ontology analysis shows that multiple pathways are expressed in the Ugandan goat breeds, which may indicate an adaptation to varied environmental conditions.…”
Section: Gene Enrichment Analysissupporting
confidence: 92%
“…There were ve (Rsb = 3, iHS = 2) candidate regions that spanned no annotated genes ( Supplementary Table S2). Such regions have been designated as "gene deserts" and have also been reported by other investigators [12,13,14,15]. Genome-wide, we identi ed 258 genes (di = 13, Rsb = 115, iHS = 130) mapping to 36 (di = 4, Rsb = 19, iHS = 13) candidate selection regions that were de ned by 287 signi cant SNPs ( Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 65%
“…The grouping was based on a priori knowledge of the breeding history and geographic-environmental origin of the breeds. Such a pooling strategy has been implemented previously [13,15,37]. Sample pooling offers several advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-population analyses of the six fat- vs. thin-tail groups (Table 1) were performed using the Extended Haplotype Homozygosity (EHH) – derived statistic Rsb [15], as in Bahbahani et al [1617]. To identify statistically significant SNPs under selection in each of the six pair-wise comparisons (positive Rsb value), one-sided P -values (fat- vs. thin-tail group) were derived as −logl0(1-Φ( Rsb )), where Φ( Rsb ) represents the Gaussian cumulative distribution function.…”
Section: Methodsmentioning
confidence: 99%